2012
DOI: 10.2341/11-417-s
|View full text |Cite
|
Sign up to set email alerts
|

Periapical Healing After Direct Pulp Capping With Calcium-enriched Mixture Cement: A Case Report

Abstract: SUMMARY This article describes a successful direct pulp capping of a mature symptomatic mandibular second molar in a 14-year-old girl. The patient was referred with sensitivity to cold beverages and pain on chewing on the second left mandibular molar. Clinical examinations revealed extensive coronal caries and sensitivity to percussion. Radiographically, the tooth was mature and had a widened apical periodontal ligament (PDL) and a narrow periapical lesion. The concluding diagnosis was symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
(36 reference statements)
0
7
0
1
Order By: Relevance
“…Radyografik olarak periapikal lezyon iyileşip kemik dolumu görülmüştür ve periodontal ligament normal kalınlığına ulaş-mıştır. 58 Haghgoo ve ark. ortodontik olarak çekilecek olan kanin dişlerine CEM materyali ve nano-hidroksiapatit (NHA) materyali ile direkt kuafaj yapıp histolojik olarak değerlendirmişlerdir.…”
Section: Pulpa Kapaklamasıunclassified
“…Radyografik olarak periapikal lezyon iyileşip kemik dolumu görülmüştür ve periodontal ligament normal kalınlığına ulaş-mıştır. 58 Haghgoo ve ark. ortodontik olarak çekilecek olan kanin dişlerine CEM materyali ve nano-hidroksiapatit (NHA) materyali ile direkt kuafaj yapıp histolojik olarak değerlendirmişlerdir.…”
Section: Pulpa Kapaklamasıunclassified
“…[47] A case report of a mature first mandibular molar with symptomatic irreversible pulpitis/apical periodontitis demonstrated favorable clinical/radiographic outcomes such as complete resolution of the apical lesion at a follow-up after 15 months. [91] Recent DPC outcomes of prospective randomized controlled/clinical trials carried out on 32 permanent teeth that were orthodontically planned for extraction have shown that under immunohistochemical examinations, thickness of dentinal bridge beneath CEM was higher than MTA at various time intervals; pulp inflammation was also lower in the CEM groups. [92] In addition, expression of fibronectin/tenascin in the CEM groups were higher than the MTA groups during both time intervals; however, the above differences were not statistically significant.…”
Section: Dpc With Cem Cementmentioning
confidence: 99%
“…The most famous materials used for this purpose include calcium hydroxide, resins, resin-modified glass-ionomer cements and mineral trioxide aggregate (MTA). In addition, lasers 2 and bioactive agents such as CEM cement 3 , 4 are innovative techniques that stimulate pulpal defense mechanisms.Calcium hydroxide was once considered the standard for pulp capping materials. The major disadvantage of Ca(OH) 2 is its dissolution over time.…”
Section: Introductionmentioning
confidence: 99%